Scanning Electron Microscopic/Energy-Dispersive X-Ray Analysis in Cases of Apical Periodontitis Refractory to Endodontic Treatment: A Case Series Study - Tavares, Warley Luciano Fonseca; Rezende, Taia Maria Berto; da Silva, Ingrid Gracielle Martins; Corrêa, Raimundo Raimundo; Henriques, Luiz Carlos Feitosa; Sobrinho, Antônio Paulino Ribeiro (Iranian Endodontic Journal, 2019)
This study aimed to present a case series of refractory endodontic treatment leading to persistent apical periodontitis. All cases were submitted to scanning electron microscopic/energy-dispersive X-ray analysis (SEM/EDS) of the external surface of the surgically removed samples and identification of the elements present in the specimens. Carbon, oxygen and calcium were elements present in all of the cases in this study. The presence of microorganisms in close contact with the periapical surrounding tissues induced the perpetuation of the inflammation process. Despite the presence of other elements different from those normally expected in the tissues, we may not attribute any interference in the periapical response to them. Keywords: Apical Periodontitis; Bacterial Biofilm; Endodontic Failure; Extra Radicular Infection